Hafnium nanocrystals observed in a HfTiO compound film bring about excellent performance of flexible selectors in memory integration. Issue 43 (28th October 2019) - Ye, Cong; Xu, Zhong; Chang, Kuan-Chang; Li, Lei; Lin, Xinnan; Zhang, Rui; Zhou, Yi; Xiong, Wen; Kuo, Tzu-Peng
Abstract : Hafnium nanocrystals are found and the corresponding physical models are proposed to explain the mechanism of the flexible Pt/HfTiO/ITO selector. Abstract : In this study, a HfTiO compound film on polyethylene naphthalate (PEN) has been investigated and designed as the selective layer material to fabricate flexible selector devices, since a selector is considered as a promising candidate for solving the sneak current issues in high-density memory integration. According to material analysis, hafnium nanocrystals observed in the HfTiO film play a key role in the performance improvement of the selector. The correlation between the HfTiO material and the corresponding current conduction mechanisms and the proposed physical mechanism model with hafnium nanocrystals have been thoroughly investigated to clarify and explain the enhanced selective behavior including high uniformity, excellent endurance and fast operation speed. Moreover, the selector with the HfTiO film exhibits superior bending reliability with no working performance degradation under a bending radius ranging from 50 mm to 30 mm, indicating the excellent flexibility and applicability of the selector in flexible application scenarios. These achievements of the Pt/HfTiO/ITO selector induced by the HfTiO film with hafnium crystals offer great potential for material and interface design in future memory integration and flexible applications.